High level of visfatin and the activation of Akt and ERK1/2 signaling pathways are associated with endometrium malignant transformation in polycystic ovary syndrome. (1st February 2020) - Tian, Wenyan; Zhang, Huixia; Zhang, Yan; Wang, Yingmei; Zhang, Yanfang; Xue, Fengxia; Song, Xueru; Zhang, Huiying
Abstract: This study aimed to assess the clinicopathological significance of serum levels and endometrium tissue expression of visfatin in polycystic ovary syndrome (PCOS) patients. A total of 80 PCOS patients and 80 matching controls were included in this study. We analyzed the relationship between the expression of visfatin in endometrium and clinicopathological characteristics in PCOS patients. The correlation between the expression of visfatin and p-Akt, Akt, p-ERK1/2, and ERK1/2 in PCOS tissues was evaluated as well. Visfatin expression in PCOS endometrial tissues were significantly higher than those in controls ( p  = .001). The expression of phosphorylation of Akt and ERK1/2 were significantly higher in PCOS endometrium tissues compared to controls ( p  < .05). Moreover, a high expression of tissue visfatin in PCOS tissues was positively correlated with the expression of p-Akt ( p  = .015), and p-ERK1/2 ( p  = .013). Western blotting revealed that protein expression of visfatin in PCOS patients with endometrial hyperplasia and cancer was higher than that in patients with normal endometrium tissues, and the difference was statistically significant ( p  = .027). The expression of p-Akt ( p  = .018) and p-ERK1/2 ( p  = .035) in PCOS patients with endometrial hyperplasia and cancer was significantly higher than that in patients with normal endometrium tissues. Visfatin may be a potential biomarker for endometrial malignant transformation in PCOS patients.